The Magnolia sisters [large type] - Major, Michelle (Major, Michelle. Magnolia sisters series., 2020)
"Avery Keller arrives in Magnolia, North Carolina, with one aim: collect her inheritance and quickly put the quirky town in her rearview mirror. But the father who didn't acknowledge her when he was alive has left Avery a mess to sort through--along with two half sisters she's never met and a gorgeous single dad living next door. Soon her plan to keep this colorful, close-knit community at a distance gets complicated.... Grayson Atwell has rescued plenty of people in his firefighting career. His work and his little girl, Violet, are his entire world and there's no time for anything--or anyone--else. But the vulnerability beneath Avery's prickly facade brings out a fiercely protective side of him. Despite her protests, Gray can see that Avery's falling under Magnolia's spell--just like he's falling for her. Now the only question is: How can he convince her to give them both a chance at forever?"--